2020
DOI: 10.1007/s10900-020-00921-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression, Anxiety, Distress and Insomnia and Related Factors in Healthcare Workers During COVID-19 Pandemic in Turkey

Abstract: The purpose of this study was to evaluate the prevalence of depression, anxiety, distress, and insomnia and related factors in healthcare workers during the COVID-19 pandemic in Turkey. We applied the study survey online to HCWs during the pandemic in Turkey between 23 April and 23 May 2020. We used the sociodemographic data form, Patient Health Questionnaire-9, General Anxiety Disorder-7, Insomnia Severity Index, and Impact of Event Scale-Revised. Six hundred twenty (66.0%) of the 939 HCWs taking part in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
238
17
22

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(302 citation statements)
references
References 49 publications
25
238
17
22
Order By: Relevance
“…A review reported that as the professional experience increased, HCWs were less likely to develop psychiatric disorders ( 38 ). Contrary to this, a Turkish study observed depression and anxiety scores in participants working for 10 years or more were significantly higher than those working for <10 years ( 36 ). In our study, we did not find any association between psychological distress and location, unlike other studies where they found HCWs living in the Central region (Riyadh) reported higher scores for anxiety and depression compared to other regions ( 20 ).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…A review reported that as the professional experience increased, HCWs were less likely to develop psychiatric disorders ( 38 ). Contrary to this, a Turkish study observed depression and anxiety scores in participants working for 10 years or more were significantly higher than those working for <10 years ( 36 ). In our study, we did not find any association between psychological distress and location, unlike other studies where they found HCWs living in the Central region (Riyadh) reported higher scores for anxiety and depression compared to other regions ( 20 ).…”
Section: Discussionmentioning
confidence: 80%
“…A study by Aoun et al ( 33 ) also reported significantly higher levels of anxiety in nurses compared to physicians. In other studies, it was observed that female nurses with close contact with COVID-19 patients appeared to suffer from the highest mental health risks ( 3 , 36 , 38 ). A Chinese study had reported that being a physician was a protective factor against insomnia ( 37 ).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations